2017
DOI: 10.1902/jop.2016.160276
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Buccal Dehiscence During Immediate Implant Placement Using the Flapless Technique: A Tomographic Evaluation

Abstract: Immediate implant placement at dehiscence buccal bone sites using flapless surgery combined with xenograft blocks provided complete formation of the buccal bone wall up to the implant shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In reconstruction and restorative treatments after tooth extraction where buccal plate has been affected, flapless immediate implants with simultaneous reconstruction of the alveolar facial bone wall, filling of the residual defect and implant-supported provisional immediate dental replacement (FIIR&P) can play an important role. However, the scarce evidence to this respect is based on case series (Assaf et al, 2017;Kan et al, 2007;Noelken et al, 2011;Rosa et al, 2014;Sarnachiaro et al, 2016;Slagter, Meijer, Bakker, Vissink, & Raghoebar, 2016;Tripodakis et al, 2016) mostly of retrospective nature or on clinical cases (Albiero et al, 2014;de Molon et al, 2015) evaluating a small number of implants (114 in 109 patients), with great methodological and clinical heterogeneity and variable follow-up periods ranging from 6 to 60 months. Despite this, most studies share the type of osseous dehiscence to be treated (Elian Type II sockets), the use of conical implants and post-extraction flapless immediate implant placement with gap-filling methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In reconstruction and restorative treatments after tooth extraction where buccal plate has been affected, flapless immediate implants with simultaneous reconstruction of the alveolar facial bone wall, filling of the residual defect and implant-supported provisional immediate dental replacement (FIIR&P) can play an important role. However, the scarce evidence to this respect is based on case series (Assaf et al, 2017;Kan et al, 2007;Noelken et al, 2011;Rosa et al, 2014;Sarnachiaro et al, 2016;Slagter, Meijer, Bakker, Vissink, & Raghoebar, 2016;Tripodakis et al, 2016) mostly of retrospective nature or on clinical cases (Albiero et al, 2014;de Molon et al, 2015) evaluating a small number of implants (114 in 109 patients), with great methodological and clinical heterogeneity and variable follow-up periods ranging from 6 to 60 months. Despite this, most studies share the type of osseous dehiscence to be treated (Elian Type II sockets), the use of conical implants and post-extraction flapless immediate implant placement with gap-filling methods.…”
Section: Discussionmentioning
confidence: 99%
“…principles (Harris et al, 2002(Harris et al, , 2012 and (b) because CBCT technology does not offer enough reliability to detect narrow alveolar crests (Gonzalez-Martin et al, 2016). Nevertheless, several authors used control CBCTs to assess the "radiographic reconstruction" and/ or the "buccal plate evolution" in this type of techniques, observing good results (Albiero et al, 2014;Assaf et al, 2017;de Molon et al, 2015;Noelken et al, 2011;Rosa et al, 2014;Sarnachiaro et al, 2016;Slagter et al, 2016;Tripodakis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from clinical studies have shown a high risk of midfacial recession following immediate implant placement in cases of an incomplete buccal bone wall . However, case series studies have reported reconstitution of the absent labial bone plate through different techniques . Because of this, hard and soft tissue augmentation procedures have been proposed to minimize buccal bone resorption and to maintain the soft tissue volume following tooth extraction .…”
Section: Introductionmentioning
confidence: 99%